Reasons for discontinuation of reversible contraceptive methods by women with epilepsy. (3rd April 2017) - Mandle, Hannah B.; Cahill, Kaitlyn E.; Fowler, Kristen M.; Hauser, W. Allen; Davis, Anne R.; Herzog, Andrew G.
Summary: Objective: To report the reasons for discontinuation of contraceptive methods by women with epilepsy (WWE). Methods: These retrospective data come from a web‐based survey regarding the contraceptive practices of 1, 144 WWE in the community, ages 18–47 years. We determined the frequencies of contraceptive discontinuations and the reasons for discontinuation. We compared risk ratios for rates of discontinuation among contraceptive methods and categories. We used chi‐square analysis to test the independence of discontinuation reasons among the various contraceptive methods and categories and when stratified by antiepileptic drug (AED) categories. Results: Nine hundred fifty‐nine of 2, 393 (40.6%) individual, reversible contraceptive methods were discontinued. One‐half (51.8%) of the WWE who discontinued a method discontinued at least two methods. Hormonal contraception was discontinued most often (553/1, 091, 50.7%) with a risk ratio of 1.94 (1.54–2.45, p < 0.0001) compared to intrauterine devices (IUDs), the category that was discontinued the least (57/227, 25.1%). Among all individual methods, the contraceptive patch was stopped most often (79.7%) and the progestin‐IUD was stopped the least (20.1%). The top three reasons for discontinuation among all methods were reliability concerns (13.9%), menstrual problems (13.5%), and increased seizures (8.6%). There were significant differences among discontinuation rates and reasons when stratified by AED category for hormonal contraception but not for any other contraceptive category. Significance: Contraception counseling for WWE should consider the special experience profiles that are unique to this special population on systemic hormonal contraception.